(untitled) (Quinto Sol, 2018)
The interview with José Emilio Burucúa and Hilda Sabato that we present was conducted on August 31, 2017. That same day, the interviewees had arrived in the city of Santa Rosa –La Pampa- with the dual purpose of holding a keynote address "Violence in history: two approaches" and to participate as commentators of the Workshop: "Politics, war and violence in the Atlantic space (16th-19th centuries)", which took place at the Faculty of Human Sciences of the National University of La Pampa. We wanted to take advantage of their visit to learn about their latest work (in particular Sabato’s recent book: Republics of the New World); consult them about their dissertation on violence and to give us a current overview of historiography at a global level and the situation of our main research institutions (the university and CONICET).